AN ASSESSMENT OF THE DISPLACEMENT OF A CAM FOLLOWER USING REGULA FALSI METHOD - KOLAWOLE ADESOLA OLADEJO; DARE ADERIBIGBE ADETAN; ADEKOLA OLAYINKA OKE; RAHAMAN ABU; GANIU AYOOLA LAMID (Journal of Engineering Studies and Research)
Cam is a mechanical component that transforms circular motion to reciprocating motion by using mating component, called the follower. The principal aim of this work was to study and analyse the displacement of a cam-follower with Regula Falsi method and verify its input by using MATLAB and FORTRAN simulations. A study was conducted on angle of rotation and the displacement of the follower, which is equal to the radius of the cam given as transcendental equation to find the exact solution. The parameters such as initial guess, final guess, iteration counter and the desired displacement are involved in finding the angular displacement to the cam system in high speed rotation. The analysis was done using a computer programming that enables verification of the results obtained and ascertaining whether the inputs are correct or not for the displacement in cam follower system. The computer output showed results of the two data sets that yielded solutions and two that did not. The results revealed that the programme could be used to find the angular displacement corresponding to a given follower displacement for any cam; if the function CAMF is modified to include the appropriate radius function, r(x). The results further revealed that at a halve cycle of a rotating cam, which is equivalent to (x = 3.142 rad), is a solution that would provide the desired displacement of the follower (opening and closing of valves).